Prevalence of hepatitis C virus infection among HIV+ men who have sex with men: a systematic review and meta-analysis. (February 2017) - Jordan, Ashly E; Perlman, David C; Neurer, Joshua; Smith, Daniel J; Des Jarlais, Don C; Hagan, Holly
Since 2000, an increase in hepatitis C virus infection among HIV-infected (HIV+) men who have sex with men has been observed. Evidence points to blood exposure during sex as the medium of hepatitis C virus transmission. Hepatitis C virus prevalence among HIV + MSM overall and in relation to injection drug use is poorly characterized. In this study, a systematic review and meta-analysis examining global hepatitis C virus antibody prevalence and estimating active hepatitis C virus prevalence among HIV + MSM were conducted; 42 reports provided anti-hepatitis C virus prevalence data among HIV + MSM. Pooled prevalence produced an overall anti-hepatitis C virus prevalence among HIV + MSM of 8.1%; active HCV prevalence estimate was 5.3%–7.3%. Anti-hepatitis C virus prevalence among injection drug use and non-injection drug use HIV + MSM was 40.0% and 6.7%, respectively. Among HIV + MSM, hepatitis C virus prevalence increased significantly over time among the overall and non-injection drug use groups, and decreased significantly among injection drug use HIV + MSM. We identified a moderate prevalence of hepatitis C virus among all HIV + MSM and among non-injection drug use HIV + MSM; for both, prevalence was observed to be increasing slightly. Pooled prevalence of hepatitis C virus among HIV + MSM was higher than that observed in the 1945–1965 US birth cohort. The modest but rising hepatitis C virus prevalence among HIV + MSM suggests an opportunity to control HCV among HIV + MSM; this combined with data demonstrating a rising hepatitis C virus incidence highlights the temporal urgency to do so.